REKONSTRUKSI KEBERLANJUTAN BUDAYA BERBASIS DEEP LEARNING UNTUK EFIKASI DIRI SISWA - Syafawani, Nurul Amatullah; Suci, Ulan; Puteri, Analia Kurnia; Kamilah, Tuti'atul; Febrianto, Priyono Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the integration of local wisdom and deep learning in social studies learning to improve students’ self-efficacy and cultural awareness. This research uses a literature study method by analyzing various relevant scientific journals. The results show that local wisdom-based learning can increase students' cultural awareness and character, while deep learning can improve engagement, critical thinking, and self-efficacy. However, most studies still discuss these approaches separately. Therefore, integrating both approaches is important to create meaningful and innovative learning. This study concludes that the integration of local wisdom and deep learning has great potential to support cultural sustainability and improve students’ competencies.